Electroencephalogram and first episode afebrile seizure in children - Ghosh, Aniruddha; Mukhopadhyay, Maya; Mukhopadhyay, Swapan (International Journal of Research in Medical Sciences, 2017)
Electroencephalogram has long been an integral part of evaluation of a child with first episode of afebrile seizure. Several studies have backed up its routine use in pediatric neurology till date and management guidelines also have adopted it. But as evidences are accumulating, it has been shown that some researchers are opining against its routine use due to reasons like need for sedation in uncooperative smaller children, inter-observer variability, abnormal tracings found in normal children, normal tracings observed in epileptic children etc. In this article authors have tried to discuss evidences showing different aspects of the debates in support and against the use of electroencephalogram in first afebrile seizure episode in children.